Firearm violence victimization among youth and young adults: A socio-ecological analysis of risk and protective factors - Taylor, Bruce G.; Lancaster, Caroline; Mumford, Elizabeth A.; Sheridan-Johnson, Jackie; Carter, Chandler C.; Mitchell, Kimberly J.; Liu, Weiwei (Preventive medicine, 2025)
To examine individual, interpersonal, community/societal, and policy-level risk and protective factors associated with firearm violence victimization (FVV) among persons 10–34 years old, and to assess age group differences in these associations. Participants (n = 5311) were drawn from the AmeriSpeak panel (September 2023–January 2024), a nationally representative United States sample. Data sources included online surveys, the U.S. Census, FBI crime reports, and a state firearm law database. Structural equation modeling assessed multi-level influences on FVV, incorporating firearm access, carrying, and attitudes (FACSA), prior victimization, and other social, policy, and demographic factors. Interaction terms were used to assess age differences (10–17 years old versus 18–34 years old). In the fully specified model, only two variables—FACSA and Juvenile Victimization, Perpetration, and Trauma History (JVPTH) —remained statistically significant predictors of FVV. Permissive firearm laws indirectly elevated FVV risk by increasing firearm exposure. Age-stratified interactions showed no statistically significant differences in predictors between youth and young adults. This suggests that FACSA and JVPTH risk factors operate similarly across developmental stages. Firearm-related behaviors and early-life trauma are central drivers of FVV. These two factors accounted for the greatest risk when controlling for other influences. Policy Implications: Prevention strategies should integrate early-life trauma intervention, firearm behavior education, and structural reforms to prevent FVV. Also, violence interruption strategies targeted toward young persons with histories of victimization could help prevent FVV. Addressing upstream firearm access and trauma exposure is critical to reducing FVV risk across developmental stages. •Firearm access, carrying, and attitudes strongly predict firearm violence.•Prior exposure to violence and trauma significantly increases firearm violence.•Permissive gun laws increase victimization indirectly by elevating gun exposure.•The identified risk factors operate similarly across developmental stages.•Prevention needs to integrate early-life trauma intervention and firearm behavior education.